Superior Epigastric Artery Perforator Flap: Anatomy, Clinical Applications, and Review of Literature - Hamdi, Moustapha; Craggs, Barbara; Stoel, Anne-Marie; Hendrickx, Benoit; Zeltzer, Assaf (Journal of Reconstructive Microsurgery, 2014)
Introduction To reduce donor site morbidity in anterior chest wall reconstruction, a flap based on perforators of the superior epigastric artery (SEA) was developed and successfully applied in a pedicled fashion for locoregional soft-tissue reconstruction.Materials and Methods We combined our anatomical and clinical experience with superior epigastric artery perforator (SEAP) flap with a PubMed search of the English language literature for articles published on “SEAP flap”. Reference lists of the articles found were then checked for other related articles of interest. Articles were compared looking at flap indication, preoperative imaging, perforator morphology, SEA integument area, surgical approach, and outcome of the flaps.Results The four best perforators were most frequently encountered in an area 2 to 6 cm from the midline and 0 to 10 cm below the xiphoid process. The territory of the SEAPs depends on the location of the perforator. Controversy exists in the current literature concerning preferable SEAP flap orientation. Although tip necrosis is the major complication, this can often be treated conservatively without affecting outcomes or can even be avoided by limiting flap length to the anterior axillary line and the zone below the midpoint between the xiphisternum and the umbilicus.Conclusion The SEAP flap provides a useful approach for reconstruction of defects of the anterior chest, or of the abdominal wall. As a perforator or adipocutaneous flap, the flap is reliable and easy to raise, and spares donor site morbidity.
Keywords: perforator flap; superior epigastric artery perforator flap; chest wall reconstruction